Prospective Genomic Profiling Study in Sarcoma Patients - Gwo Fuang Ho; E Von Cheong; Wei Ying Chye; Kein Seong Mun; Rozita Abdul Malik; Marniza Saad (Indian Journal of Medical and Paediatric Oncology, 2025)
Introduction Sarcoma is a heterogenous group of malignancy with diverse pathology and clinical behavior. Survival rates differ among histological subtypes, but overall prognosis remains poor due to the scarcity of effective systemic therapies. An insight into the genomic characteristics of different sarcoma histological subtypes enhances our understanding of the disease and highlights potential targeted therapies.